Novel synergism of two antifungal agents, copiamycin and imidazole. - Uno, J (1983)
Copiamycin, a macrocyclic lactone antifungal antibiotic, was found to potentiate the antifungal effect of imidazole compounds, ketoconazole in particular. The potentiation of two nominally fungistatic agents in vitro was substantiated by a marked reduction of the minimum inhibitory and minimum fungicidal concentrations when the drugs were used in combination. The effectiveness of this synergistic combination was also demonstrated in experimental murine candidosis. Evidence is presented to suggest that this combined effect is due, at least in part, to the ionophoretic property of copiamycin. Whereas amphotericin B induces a marked increase in cellular permeability, this antibiotic does not possess the ionophoretic action of copiamycin, indicating that the enhancement of copiamycin activity and significant reduction of amphotericin B activity by ketoconazole pretreatment can be ascribed not only to changes in membrane permeability of the test organisms, but also to the different action mechanisms of copiamycin and amphotericin B. It is thus plausible that the strong synergism of copiamycin with imidazole compounds is related to the ionophoretic activity of the antibiotic. Further studies on the biochemical mechanism of this synergistic effect are being conducted together with an assessment of the clinical significance of this drug combination.